Oxygen uptake kinetics and biological age in relation to pulling force and 400-m front crawl performance in young swimmers - Strzala, M.; Sokolowski, K.; Wadrzyk, L.; Staszkiewicz, R.; Kryst, L.; Zeglen, M.; Krezalek, P.; Maciejczyk, M. (Frontiers in Physiology, 2023)
Background: The study aimed to assess differences in the biological age (BA) of 13-year-old swimmers and show their ability, as biologically younger—late mature or older—early mature, to develop fast 60-s oxygen uptake (VO2) kinetics and tethered swimming strength. Furthermore, the interplay between swimming strength, VO2, and 400-m front crawl race performance was examined.